2013
DOI: 10.1002/jobm.201300308
|View full text |Cite
|
Sign up to set email alerts
|

Mercuric reductase activity of multiple heavy metal‐resistant Lysinibacillus sphaericus G1

Abstract: A culture was isolated from an industrial mercuric salt-contaminated soil, which could tolerate Cd, Co, Zn, Cr, and Hg up to 190, 525, 350, 935, and 370 μM, respectively. The isolate was identified as Lysinibacillus sphaericus by 16S rRNA gene sequencing. It bioaccumulated Cd, Co, and Zn, and reductively detoxified Cr and Hg. Chromate reductase and mercuric reductase (MerA) activities in the cell extract were 2.4 and 0.13 units mg(-1) protein, respectively. The study also describes designing of broad-specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Similarly, two Lysinibacillus strains (L. xylanilyticus and L. marcoides) showed promising results in reducing toxic Se oxyanions into elemental Se nanoparticles [52]. In addition, Bafana et al [53] reported that L. sphaericus can detoxify Cr and Hg by reducing them. The second mechanism is biosorption, which is the binding of metal ions with metal-binding proteins present on the bacterial cell wall.…”
Section: Potential As a Metal Bioremediation Agentmentioning
confidence: 99%
“…Similarly, two Lysinibacillus strains (L. xylanilyticus and L. marcoides) showed promising results in reducing toxic Se oxyanions into elemental Se nanoparticles [52]. In addition, Bafana et al [53] reported that L. sphaericus can detoxify Cr and Hg by reducing them. The second mechanism is biosorption, which is the binding of metal ions with metal-binding proteins present on the bacterial cell wall.…”
Section: Potential As a Metal Bioremediation Agentmentioning
confidence: 99%
“…Although the reduction pathway was not studied here, it is suggested that a rapid reduction of Au(III) to Au(I) occurs in the cell wall and is followed by a slow reduction to Au(0) [30]. This reduction pathway could compromise the S-layer [31] and a mer-like cluster, the latter of which confers microbial resistance to mercury by reducing the toxic metal to Hg(0) with the reductase enzyme, MerA [32]. This enzyme could also work on gold species due to the similarities between the metals [30].…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial model strains were selected to assess the differential influence of NPs on antimicrobial activity considering their distinct cell wall architectures. Both bacterial strains are known for their resistance to environmental stress, such as heavy metal or antibiotic exposure, which make them suitable models for studying bacterial drug resistance. Notably, S.…”
Section: Methodsmentioning
confidence: 99%